THE INFLUENCE OF THE IMPLEMENTATION OF ISLAMIC RELIGIOUS EDUCATION ON STUDENTS' HONESTY BEHAVIOR IN SCHOOLS - Delpina Harahap, Ruwaida ruwaidah, Syahrul Budiman (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2025)
This study aims to determine the Influence of Islamic Religious Education on the HonestBehavior of Students at Siti Banun Sigambal Private Vocational School, both by Test and NonTest. The population in this study is Class X students of Siti Banun Sigambal Private VocationalSchool. The number of samples was determined using the arikunto formula with a total of 26people and the analysis methods used were the Test analysis method, Test Validity Test,Reliability, and Hypothesis Test. From the results of the validity test, it can be seen that eachquestion item has a r calculation > from the r table (0.317) and a positive value so that thequestion item is declared valid. The results of the Reliability test can also be seen if eachvariable has a Cronbach alpha value of more than 0.60 (a > 0.60), with a value of variable X asmuch as (0.749) and variable y as much as (0.767) so that it can be concluded that all variablesX and Y are reliable. The results of the partial hypothesis test (t-test) show that Islamic ReligiousLearning has an influence and significance on the honest behavior of Class X students of SitiBanun Sigambal Private Vocational School. The results of the hypothesis test were obtained thatthe tcal> ttable was 2.013 > 1.710, then H0 was rejected and Ha was accepted, so that therewas a significant influence between Islamic Religious Learning on Students' Honest Behavior atSiti Banun Sigambal Private Vocational School.